2013
DOI: 10.1080/19452829.2013.827637
|View full text |Cite
|
Sign up to set email alerts
|

Aspirations and Human Development Interventions

Abstract: What role can aspirations play in small-scale human development interventions? In this paper, we contribute to answering that question with both conceptual and empirical work. Aspirations can play at least two roles in small-scale human development interventions: the capabilities-selecting role and the agencyunlocking role. While aspirations also face the challenge of adaptation to adverse circumstances and unjust social structures, we argue that this challenge can be met by embedding the formulation and expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(48 citation statements)
references
References 23 publications
1
46
1
Order By: Relevance
“…There is a need to for Somali diasporic youth to have a place to imagine and reimagine their futures with adults and peers who allow them to change their minds and even contradict themselves. Aspirations are not a linear process from present to future; but instead are dynamic, socially and culturally constructed, and likely to change as youth develop and engage in new social environments (Conradie & Robeyns, 2013;DeJaeghere 2018). Discussions, mentoring, and hands-on learning experiences around the topic of aspirations that span a period of time give youth opportunities to maintain an orientation toward the future throughout their development and create the conditions for the "birth of new aspirations" or the "discovery of latent aspirations" (Conradie & Robeyns, 2013, p. 562).…”
Section: Implications For Practicementioning
confidence: 99%
“…There is a need to for Somali diasporic youth to have a place to imagine and reimagine their futures with adults and peers who allow them to change their minds and even contradict themselves. Aspirations are not a linear process from present to future; but instead are dynamic, socially and culturally constructed, and likely to change as youth develop and engage in new social environments (Conradie & Robeyns, 2013;DeJaeghere 2018). Discussions, mentoring, and hands-on learning experiences around the topic of aspirations that span a period of time give youth opportunities to maintain an orientation toward the future throughout their development and create the conditions for the "birth of new aspirations" or the "discovery of latent aspirations" (Conradie & Robeyns, 2013, p. 562).…”
Section: Implications For Practicementioning
confidence: 99%
“…Thus, a "capability to aspire" (Powell, 2012;McGrath and Powell, 2015) is essential if other capabilities are to be realised. This account has been developed usefully through a number of empirical studies from Africa, by Ibrahim (2011) on Egypt, by Conradie and Robeyns (2013) and Powell (2012;2014) on South Africa, and by Dejaeghere and Baxter (2014; on Uganda and Tanzania. Conradie and Robeyns (2013) argue that if people have low aspirations, then they may believe that certain capabilities are unavailable even if they are achievable, if only implausibly.…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%
“…Through an overview and comparison of research in the health field and a summary narrative analysis of studies across identified thematic groups, the review finds a number of different interpretations as to what capabilities to focus on depending on the intervention under consideration. Although this can be argued to be one of the benefits of the capability approach, drawing from the “toolbox” to suit a given research question (Conradie and Robeyns 2013), it also leads to practical difficulty. Mitra et al (2013) summarise this problem neatly:

Although there is conceptual value to its voluntary incompleteness, Sen’s approach makes the capability approach difficult to operationalize (Mitra et al 2013)

This study provides an overview as to how researchers are attempting to measure capability and inform decision and policy making, particularly in the health field.…”
Section: Discussionmentioning
confidence: 99%